Genomic variability of Cirneco dell'Etna and the genetic distance with other dog breeds. Issue 1 (1st January 2021) - Cortellari, Matteo; Bionda, Arianna; Talenti, Andrea; Ceccobelli, Simone; Attard, George; Lasagna, Emiliano; Crepaldi, Paola; Liotta, Luigi
Abstract: Cirneco dell'Etna is an old Italian breed of scent hunting dogs. Commonly used genomic measures such as heterozygosity, fixation indexes, and runs of homozygosity can help to improve knowledge about its genetic diversity. This study aimed to: (i) investigate Cirneco's genomic background, (ii) quantify its genomic inbreeding, and (iii) detect genomic regions differentiating the Cirneco's two allowed coat colours, self-coloured fawn and tan and white. Canine 230 K SNP BeadChips was used to investigate 24 Cirneco (19 self-coloured fawn, and 5 tan and white) and other 106 dogs from eight phylogenetically and historically related breeds. The genetic distance, ancestry, and relationship among breeds were explored by multidimensional scaling, Reynolds distances, phylogenetic tree, and admixture analysis. The genomic inbreeding ( F ROH ) was calculated for each breed. Averaged Wright's fixation index F ¯ ST was used to identify the genes that most differentiated the two groups of Cirneco. All analyses highlighted that Segugio Italiano and Kelb tal Fenek are the closest breeds to Cirneco. Within the breed, tan and white subjects showed a more heterogeneous genetic background and a lower inbreeding in comparison with self-coloured fawn ones, even though more than half of the latter presented a superimposable admixture. The gene that most differentiated these two groups is Microphthalmia-Associated Transcription Factor ( MITF ), previously associated with white spotting in other breeds. Given the small size of the Cirneco population and its open registry, its management should carefully combine morphological and genealogical evaluations with genetic tools to identify the best breeders while maintaining an acceptable genetic pool. Highlights: The genomic analysis demonstrated that Segugio Italiano and Kelb tal Fenek are genetically related to the Cirneco. The MITF gene is responsible for white blazing in Cirneco as in many other dog breeds. Genomic tools should be integrated with phenotypic and genealogic evaluations in the management of Italian autochthonous dog breeds to safeguard their welfare and biodiversity.